Nanoparticles of Cadmium Sulfide in Mesoporous SBA-15 Host: Preparation and Characterization - Yu, Hui; Hu, Shun; Li, Xiao-Dong; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2011)
In this research, cadmium sulfide nanoparticles were introduced into the mesoporus SBA-15 by ion exchange and hydrothermal method. Characterization by chemical analysis, infrared spectra, powder X-ray diffraction, nitrogen adsorption-desorption, scanning electron microscopy and photoluminescence study indicates that the guest cadmium sulfide has been located in the host channels of host-guest (SBA-15)-CdS nanocomposite materials. The SEM results indicated that the average size of (SBA-15)-CdS was 323 nm. The photoluminescence study revealed that at 541 nm the nonacomposite compounds (SBA-15)-CdS show luminescence and have an applied foreground as a promising luminescent material.